Insulin sensitivity across the lifespan from obese adolescents to obese adults with impaired glucose tolerance: Who is worse off?. Issue 2 (20th July 2017) - Arslanian, Silva; Kim, Joon Young; Nasr, Alexis; Bacha, Fida; Tfayli, Hala; Lee, SoJung; Toledo, Frederico G. S.
Abstract : Objective: Youth type 2 diabetes mellitus (T2DM) occurs decades earlier than adult T2DM and is characterized by high therapeutic failure rates and decreased response to insulin sensitizers suggesting a more severe disease process than in adults. To explain these observations, we hypothesized that insulin resistance is worse in obese youth than adults with impaired glucose tolerance (IGT), a state of high‐risk for T2DM. As proof‐of‐concept, we compared insulin sensitivity between BMI‐, sex‐, and race‐matched obese youth vs adults with IGT. Methods: This retrospective analysis of IGT youth and adults included 34 obese adolescents matched (2:1) for BMI, sex, and race to 17 adults. Hepatic and peripheral insulin sensitivity were measured by [6, 6‐ 2 H2 ]glucose and hyperinsulinemic‐euglycemic clamp. Body composition (DEXA) and serum lipid profile were examined. Results: Despite similar percent body fat, obese adolescents had 2‐fold higher fasting insulin concentration, lower hepatic (~53%) and peripheral (~42%) insulin sensitivity and lower HDL compared with adults (all P < .01). Surrogate estimate of insulin sensitivity, 1/fasting insulin was lower and HOMA‐IR was higher in adolescents vs adults. Adults had a more atherogenic lipid profile with higher total‐, LDL‐, and non‐HDL cholesterol. Conclusions: Obese youth and adults with IGT differ in that youth are more insulin resistant than adults in spite of similar adiposity. This could potentially explain the earlier onset of T2DM in youth through an early and amplified burden on a β‐cell destined to decompensate, and explicate their lower therapeutic response to insulin sensitizers.